(3edJbWGJ ef GdQSGdI GdeThbIs - (3CHh GdaQL gfOhs
(3ChdgG (B:s
(3edJbWGJ ef GdQSGdI GdeThbI dGHi GdaQL gfOh s
(3BNQgG (B:s
(3Ke CKHJ ai BNQ GdUfGYI dGfgG ai ZGjI GdNaG hGdZehV s
(3ajg SHYI aUhds
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3QVG QGeHhQ (B(284(9)) s
Keywords: (3GdadSaI hGdefWbs